Comparison of Diameters of Ipsilateral and Contralateral Foramen Spinosum in Patients with Supratentorial Meningiomas - Saylısoy, Suzan; Öztürk, Saffet; Öztürk, Esin (Cerrahpaşa Medical Journal, 2020)
Objective: Most of the supratentorial meningiomas is supplied by the middle meningeal artery (MMA) that enters the cranial cavity through the foramen spinosum. We aimed to analyze the maximal diameters of ipsilateral and contralateral foramen spinosa in patients with supratentorial meningioma, and to investigate whether the enlargement of foramen spinosum (FS) at ipsilateral side suggesting enlargement of MMA is present. Methods: A total of 44 patients who underwent brain CT examination between January 2010 and January 2016, who had supratentorial meningioma were included in this study. The maximal diameter of ipsilateral and contralateral foramen spinosa was measured and compared. Results: In 44 patients (28 women, 16 men; mean age 58.59 years, range 15-89 years), maximal FS diameter of was ranged between 1.4 and 4.4 mm (mean, 2.79±0.55 mm) at the ipsilateral side, between 1.6 and 3.4 mm (mean, 2.51±0.47 mm) at the contralateral side. The ipsilateral FS was larger than that of the contralateral with statistically significant. Conclusion: The maximal FS diameter, which is probably related to the enlargement of MMA, was significantly greater in ipsilateral sides in supratentorial meningiomas. This finding may be kept in mind in differentiating meningiomas that have atypical imaging features from other masses. Cite this article as: Saylısoy S, Öztürk S, Öztürk E. Comparison of Diameters of Ipsilateral and Contralateral Foramen Spinosum in Patients with Supratentorial Meningiomas. Cerrahpaşa Med J 2020; 44(3): 133-136.